2016
DOI: 10.2355/isijinternational.isijint-2015-307
|View full text |Cite
|
Sign up to set email alerts
|

A Microelectrochemical Approach to Understanding Hydrogen Absorption into Steel during Pitting Corrosion

Abstract: A small Devanathan-Stachurski cell was newly designed to ascertain the hydrogen absorption behavior into re-sulfurized carbon steel during pitting corrosion. In 0.1 M NaCl (pH 5.5), a pit was generated on a small area with MnS inclusions, the current of hydrogen permeation current increased sharply when the solution (capillary) was placed on the steel surface, and the current density returned to the background after the capillary was removed. On the other hand, no pitting was observed on the area without the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…(1) By virtue of cross-model, we illustrated MnS evolution, accompanied by the matrix growth of dendrites during solidification, and indicated that MnS precipitation depends on local undercooling, solutal concentration, and dendritic morphology, thus coexisting in three different shapes. (2) We found that element S played a dominant role in the concentration product and caused MnS to be precipitated at a low solid fraction and the content of Mn was a restrictive factor in deciding the amount of precipitated MnS, due to its high partition coefficient. (3) A re-precipitation of MnS was observed in a system with high content of Mn and low content of S because excessive Mn had great potential to react with residual S, which was able to form new seeds when the required reaction conditions for MnS formation could be satisfied again.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…(1) By virtue of cross-model, we illustrated MnS evolution, accompanied by the matrix growth of dendrites during solidification, and indicated that MnS precipitation depends on local undercooling, solutal concentration, and dendritic morphology, thus coexisting in three different shapes. (2) We found that element S played a dominant role in the concentration product and caused MnS to be precipitated at a low solid fraction and the content of Mn was a restrictive factor in deciding the amount of precipitated MnS, due to its high partition coefficient. (3) A re-precipitation of MnS was observed in a system with high content of Mn and low content of S because excessive Mn had great potential to react with residual S, which was able to form new seeds when the required reaction conditions for MnS formation could be satisfied again.…”
Section: Discussionmentioning
confidence: 89%
“…MnS precipitation plays an entirely different role in the performance of steel. It is seriously detrimental to intergranular cracking due to the precipitation reaction within solidifying metal acting as a strong sink of free sulfur segregation to the grain boundaries [1], thus decreasing corrosion resistance by accelerating hydrogen absorption into the matrix [2] and weakening the hot ductility because boundary sliding is enhanced at austenite grains [3]. The lower modulus and hardness of MnS inclusions compared to those of a matrix give rise to a drop in the fatigue strength of steel [4], while the machinability is amended simultaneously [5].…”
Section: Introductionmentioning
confidence: 99%
“…They directly observed the promotion of hydrogen entry near MnS inclusions exposed to an aqueous solution using a micro hydrogen permeation cell. 17) Under the cyclic corrosion condition, the addition of S slightly promoted hydrogen entry at lower relative humidity as shown in Fig. 16.…”
Section: Effect Of S On Hydrogen Entrymentioning
confidence: 95%
“…27) A Pd film of 100 nm in thickness was subsequently plated by physical vapor deposition because inclusions in the surfaces were not covered with the electroplated Pd film. 28) The front side of the nitrided specimens, that is the surface with the nitrided layer, was set at the hydrogen entry side. The back side of the specimens with the Pd film was set at the hydrogen detection side.…”
Section: Electrochemical Hydrogen Permeationmentioning
confidence: 99%